Impact of mechanization on costs, workers' productivity and labor-land ratio for in- field evacuation of oil palm fresh fruit bunch: a case study in Sungai Semak estate / Muhammad Noor Khairuddin Seman - Seman, Muhammad Noor Khairuddin (2018)
The issue of labor and foreign workes in the oil palm industry should be treated as a top most priority item in moving the industry forward. Despite the employment of 610635 workers of which 90 percent are foreign workers, this industry is a major contributor to the projected export earnings at RM65 billion and RM75 billion in 2010 and 2015 respectively.